Molly Moon stops the world - Byng, Georgia (New York : HarperTrophy, 2005)
Believing that she has been sent to Los Angeles by her librarian friend, Lucy Logan, to stop an evil plot by the wealthy Primo Cell, Molly Moon and her friend Roger, orphans with unusual hypnotic powers, find themselves in danger from an unsuspected source.
First published : Britian : Macmillan Children's Books, 2003.
Sequel to: Molly Moon's incredible book of hypnotism.
5.5
3-6
3-6
School Library Journal
Keywords: Moon, Molly (Fictitious character) -- Fiction; Hypnotism -- Fiction; Orphans -- Fiction; Los Angeles (Calif.) -- Fiction; Moon, Molly (Fictional character) -- Fiction; Hypnotism -- Fiction; Orphans -- Fiction; Los Angeles (Calif.) -- Fiction